Determinación del incremento en diámetro y altura de una plantación de Ocotea aciphylla “moena”, de 3 años de edad, en el CIEFOR - Puerto Almendra, Loreto – Perú. 2023 - Mesia Isuiza, Clara Isabel (2024)
A study was carried out on the increase in diameter and height in an O. aciphylla plantation at CIEFOR – Puerto Almendra. The increases in diameter and height do not present statistical differences, having similar growth in all the belts under study. The null hypothesis is accepted considering that there is no difference in the increases in diameter and height in the study strips. Until 2023, there is 77.5% survival and 22.5% mortality in O. aciphylla plants. Likewise, A total of 39 seedlings presented VERY GOOD quality, which represents 25.16% of the total, which represented 8.6% of the total, while 8 plants presented Poor quality (5.16%).